2015
DOI: 10.1289/ehp.1408188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Endocrine-Disrupting Chemical DDT on Self-Renewal and Differentiation of Human Mesenchymal Stem Cells

Abstract: Background: Although the global use of the endocrine-disrupting chemical DDT has decreased, its persistence in the environment has resulted in continued human exposure. Accumulating evidence suggests that DDT exposure has long-term adverse effects on development, yet the impact on growth and differentiation of adult stem cells remains unclear.Objectives: Human mesenchymal stem cells (MSCs) exposed to DDT were used to evaluate the impact on stem cell biology.Methods: We assessed DDT-treated MSCs for self-renewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 36 publications
(39 reference statements)
2
36
0
Order By: Relevance
“…These observations agree with the ability of p , p ′ - DDT (at 20  μ M) to induce differentiation in adipocytes 3T3-L1 and preadipocytes 3T-F442A [40]. They are also consistent with a recent study in human mesenchymal stem cells (MSCs) from bone marrow, which showed that p , p ′ - DDT exposure enhanced osteogenic and adipogenic differentiation [39]. Our work suggests that p , p ′ - DDE exposure at the concentrations found in bone marrow of humans can induce intracellular molecular pathways (ROS, PKC α , p38, and C/EBP β ) that are involved in the myeloid differentiation and, consequently, induce morphological differentiation of this human myeloid cell line.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These observations agree with the ability of p , p ′ - DDT (at 20  μ M) to induce differentiation in adipocytes 3T3-L1 and preadipocytes 3T-F442A [40]. They are also consistent with a recent study in human mesenchymal stem cells (MSCs) from bone marrow, which showed that p , p ′ - DDT exposure enhanced osteogenic and adipogenic differentiation [39]. Our work suggests that p , p ′ - DDE exposure at the concentrations found in bone marrow of humans can induce intracellular molecular pathways (ROS, PKC α , p38, and C/EBP β ) that are involved in the myeloid differentiation and, consequently, induce morphological differentiation of this human myeloid cell line.…”
Section: Discussionsupporting
confidence: 91%
“…The few in vitro experiments that have been performed demonstrate that DDT induces adipogenic and osteogenic differentiation of mesenchymal stem cells [39] and adipocyte differentiation from preadipocyte 3T3-L1 cells and increases the nuclear levels of C/EBP α , β [40]. DDT negatively affects haematic cells and their immunocompetence, but its effect on differentiation of immune cells and the mechanisms underlying these effects remain to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Many endocrine disruptors target PPARγ by binding to it directly to activate downstream cascades that lead to enhanced adipogenesis or by increasing PPARγ expression to allow for a lower threshold for activation. These EDCs include DDT, dichlorodiphenyldichloroethylene or 1,1-dichloro-2,2-bis (p-chlorophenyl)-ethylene (81), 4-NP, OP, BPA, PCB-77, DEHP, MEHP, DBP, BBP, and MBzP (35, 37, 39, 43, 63, 66, 6870, 75, 7780, 8285). Perinatal exposure to 4-NP has also been shown to increase PPARγ gene expression and sterol regulatory element-binding factor 1 (SREBF-1) expression in adipose tissue (83).…”
Section: Adipogenesismentioning
confidence: 99%
“…Thus, PPARγ and SREBF-1 are key transcriptional factors in adipogenesis. The expression of C/EBPα and expression of factors promoted by PPARγ, such as lipoprotein lipase and fatty acid binding protein 4/adipocyte protein 2 (aP2), have been shown to be increased in response to DDT, DDE, 4-NP, BPA, PCB-77, DEHP, MEHP, and BBP (37, 39, 42, 45, 46, 66, 68, 69, 73, 75, 76, 78, 8284, 8689). p , p ′-DDT has also been shown to increase binding of C/EBPα to its DNA response element, demonstrating that the promotion of adipogenesis may be occurring through both increased expression and activation of targeted receptors (66).…”
Section: Adipogenesismentioning
confidence: 99%
“…Different authors have proved DDT to be hazardous to humans by using different tests [50][51][52][53][54][55]. Shaw et al [56] presented data on pesticide residues in milk from Indonesian women which demonstrated general exposure to p,p'-DDT and hexachlorobenzene (HCB).…”
Section: Toxicity Among Humansmentioning
confidence: 99%